2020
DOI: 10.1371/journal.pone.0242345
|View full text |Cite
|
Sign up to set email alerts
|

From non-use to covert and overt use of contraception: Identifying community and individual factors informing Nigerian women’s degree of contraceptive empowerment

Abstract: Objective In Nigeria, unmet need for contraception is high despite improved access to modern contraception. To identify factors that support Nigerian women’s contraceptive decisions to achieve their reproductive goals, in the presence or absence of their partner’s support, we seek to identify individual/couple and community level determinants of a spectrum of contraceptive practices, from non-use to covert and overt use of contraception. Methods Data were drawn from a national probability survey conducted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 28 publications
(69 reference statements)
3
24
0
1
Order By: Relevance
“…Apart from husband's gender attitude and mobility, women's educational attainment, working status, parity, religion, place of residence, discordance in desire number of children are found to influence the covert contraceptive use. In India, spousal schooling and age gaps might also affect CCU as women tend to marry more educated or older men than themselves and they possibly internalized husband's high handedness in sexual and reproductive healthcare decisions, thinking the husband would make wiser decisions for them [1,2,33].…”
Section: Women's Autonomy and Contraceptive Usementioning
confidence: 99%
See 1 more Smart Citation
“…Apart from husband's gender attitude and mobility, women's educational attainment, working status, parity, religion, place of residence, discordance in desire number of children are found to influence the covert contraceptive use. In India, spousal schooling and age gaps might also affect CCU as women tend to marry more educated or older men than themselves and they possibly internalized husband's high handedness in sexual and reproductive healthcare decisions, thinking the husband would make wiser decisions for them [1,2,33].…”
Section: Women's Autonomy and Contraceptive Usementioning
confidence: 99%
“…The independent variables were categorized into two parts. The first category included women's background characteristics, women's education, religion, caste, place of residence, and wealth [5,33,39] while the second category included couple-level variables. Religion, that was included in the first category, was divided into three categories: Hindu, Muslim, and Other.…”
Section: Independent Variablesmentioning
confidence: 99%
“…However, covert use of contraceptives could highlight the discordance between women’s ability to decide on their sexual reproductive health and societal infringement of their right to choose. Previous studies in sub-Saharan Africa have shown that covert contraceptive use is associated with low levels of education [ 24 , 25 ], urban residence [ 24 , 26 ], richest wealth quintile [ 4 , 24 , 27 ] and polygamous marriage [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Covert contraceptive use is widespread in sub-Saharan Africa, with a prevalence of 2.6–53% [ 24 – 26 , 28 , 29 ]. In Kenya, previous studies based on the 2008/09 [ 24 ] and 2014 [ 1 ] demographic health survey (DHS), and in Nyanza region [ 30 ] found that 8.7, 7.8 and 9% of married women used contraceptives without their partners’ knowledge, but did not explore the associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Here we emphasize the potential role of women’s equality as a precondition for securing wellbeing and prosperity for populations, and its catalytic effect on contraceptive provision and use ( Slaymaker et al, 2020 ). To study how to overcome gender inequalities or to gain greater reproductive autonomy in restricted environments with high fertility prevalence, some studies have examined programmatic approaches to renegotiate gender relationships with promising evidence in a Mumbai slum ( Cislaghi et al, 2020 ), or the covert use of contraception among women in need of family planning in sub-Saharan Africa (SSA), where contraceptive use has been positively associated with working outside the home but negatively related to more years of schooling ( Gasca and Becker 2018 ; OlaOlorun, Anglewicz, and Moreau 2020 ). Women’s self-help groups (SHGs) is another mechanism associated with a significant impact on women’s economic, social, and political empowerment in South Asia and other developing countries ( Brody et al, 2017 ), although still with limited or no impact on psychological empowerment or on attitudes towards domestic violence and respect within households in India ( Kumar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%